2006
DOI: 10.1159/000091730
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Voice Problems in Teachers

Abstract: In order to identify factors that are associated with voice problems and voice-related absenteeism in teachers, 1,878 questionnaires were analysed. The questionnaires inquired about personal data, voice complaints, voice-related absenteeism from work and conditions that may lead to voice complaints and absenteeism. Different factors play a role in the development and consolidation of voice problems. Physical and psycho-emotional factors appear to be the most important risk factors. Remarkably, voice load and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
102
1
24

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 51 publications
5
102
1
24
Order By: Relevance
“…Years of teaching have been identified as a risk factor because of cumulative voice use. 13,14 The number of pupils in the classroom also showed to be important since teaching a larger group requires more vocal effort. 13 Abundant background noise or classrooms with bad acoustics forces the teacher to speak more loudly, which also increases the risk.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Years of teaching have been identified as a risk factor because of cumulative voice use. 13,14 The number of pupils in the classroom also showed to be important since teaching a larger group requires more vocal effort. 13 Abundant background noise or classrooms with bad acoustics forces the teacher to speak more loudly, which also increases the risk.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 The number of pupils in the classroom also showed to be important since teaching a larger group requires more vocal effort. 13 Abundant background noise or classrooms with bad acoustics forces the teacher to speak more loudly, which also increases the risk. 9 Other unfavorable working conditions, for example, dry air, dust, smoke, temperature changes, may irritate the mucosa and negatively influence the voice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated a high prevalence of voice disorders in teachers, as well as the personal, professional and economical relevance of the problem [1][2][3][4]. Moreover, some reports seem to indicate that poor voice quality in teachers reduces the intelligibility of their speech and the cognitive functioning and successful learning of the students [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Teachers have high prevalence of vocal problems when compared with other professionals who use their voice as an instrument of labor 2 .…”
Section: Introductionmentioning
confidence: 99%